Prevalence and Risk Factors of GERD among Stable COPD Patients - Muhammad Hafiz; Faisal Yunus; Maulana Suryamin; Mohammad Fahmi Alatas; Adityo Wibowo (Jurnal Respirasi, 2023)
Introduction: Gastroesophageal reflux disease (GERD) is one of the most common causes of a chronic cough and is a potential risk factor for chronic obstructive pulmonary disease (COPD) exacerbation. This study aimed to determine the prevalence of GERD in COPD patients. Methods: This was a cross-sectional study involving 40 stable COPD patients recruited from outpatient asthma and COPD clinics at Persahabatan National Respiratory Referral Hospital, Jakarta, from May to November 2018. COPD was defined as having a ratio of post-bronchodilator FEV1/FVC < 0.7 and no abnormality on a chest X-ray except emphysematous.  Diagnosis of GERD was based on oesophageal mucosal lining break surrounding the distal esophageal sphincter through esophagogastroduodenoscopy (EGD). Asthma patients with known esophageal diseases such as cancer, achalasia, and active peptic ulcer and patients who had used proton pump inhibitors in the last 15 days were excluded. Results: Patients were divided into GERD (+) (16/40, 40%) and GERD (-) (24/40, 60%). Subjects were predominantly elderly (25/40, 62.5%) and had a smoking history (36/40, 90%). Exacerbation and COPD assessment test (CAT) score was significantly associated with GERD (p < 0.05). No significant difference regarding age, sex, Brinkman Index, lung function, and body mass index (BMI) was found between groups. However, the GERD (+) group showed a slightly higher BMI and more severe airflow obstruction. Conclusion: The prevalence of GERD in COPD patients found in this study was as high as 40%. A cohort study and preventive strategy of GERD in COPD should be studied further.